Pengaruh Pengetahuan dan Sikap Pencegahan Covid-19 terhadap Perilaku Self Management Hipertensi di Desa Sukoharjo - Tutik Yuliyanti; Sri Dayaningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
The death rate of Covid-19 cases is influenced by congenital diseases, one of which is hypertension. Good knowledge and attitude to prevent Covid-19 can demonstrate health maintenance behavior. Self-management of hypertension that is applied in daily life can help maintain stable blood pressure so that it will reduce the risk of COVID-19. The purpose of this study was to analyze the effect of knowledge and attitudes to prevent COVID-19 on hypertension self-management behavior in Sukoharjo village. This type of research is descriptive analytic with a cross sectional design. The sampling technique used was purposive sampling with a sample of 42 people who had hypertension. The data analysis technique used was multiple linear regression analysis. Results: there is a significant positive effect between knowledge of Covid-19 prevention on hypertension self-management behavior. Every 1 increase in knowledge of COVID-19 prevention scores will increase by 0.01 the hypertension self-management behavior score (b<0.01, 95% CI<0.01-0.01). There is a significant positive effect between the attitude of preventing Covid-19 on hypertension self-management behavior. For every 1 increase in the Covid-19 prevention attitude score, the score for hypertension self-management behavior will increase by 0.06. (b<0.06, 95% CI<0.01-0.06). Conclusion: knowledge and attitude to prevent covid-19 affect hypertension self-management behavior.